KNOWLEDGE-BASED SIGNAL PROCESSING FOR RADAR IDENTIFICATION - Matuszewski, Jan (International Journal of Computing, 2014)
The paper presents some aspects of radar signals acquisition in the electronic intelligence (ELINT) system, the analysis of their parameters, feature extraction using linear Karhunen-Loeve transformation and applying knowledge-based techniques to the recognition of the intercepted signals. The process of final emitter identification is based on “the knowledge-based approach” which was implemented during the processing of constructing the database.